2017
DOI: 10.1039/c7nj01006k
|View full text |Cite
|
Sign up to set email alerts
|

Microwave solution route to ceramic ZnAl2O4 nanoparticles in 10 minutes: inversion and photophysical changes with thermal history

Abstract: Within 10 minutes microwave synthesis using metal complexes can form crystalline ZnAl2O4 nanoparticles with significant inversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 66 publications
2
20
0
Order By: Relevance
“…The narrow scan of Al 2p without Ar etching (on the surface, 0 nm) is shown in Figure 3b, in which the Al 2p peak was deconvoluted to two separated peaks located at 72.0 eV (blue) and 74.2 eV (red), representing tetrahedral Al 3+ and octahedral Al 3+ , respectively. 23 The formation of these two different Al 3+ species may be caused by the different local oxygen abundance in the SnO 2 @Al 2 O 3 and the effect of Sn atoms. This phenomenon was also found previously in some Al-related spinel structures.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The narrow scan of Al 2p without Ar etching (on the surface, 0 nm) is shown in Figure 3b, in which the Al 2p peak was deconvoluted to two separated peaks located at 72.0 eV (blue) and 74.2 eV (red), representing tetrahedral Al 3+ and octahedral Al 3+ , respectively. 23 The formation of these two different Al 3+ species may be caused by the different local oxygen abundance in the SnO 2 @Al 2 O 3 and the effect of Sn atoms. This phenomenon was also found previously in some Al-related spinel structures.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…Figure c,d shows the narrow scan of Al 2p peak and Sn 3d peaks at the position of different Ar etching depths in SnO 2 @Al 2 O 3 spheres. The narrow scan of Al 2p without Ar etching (on the surface, 0 nm) is shown in Figure b, in which the Al 2p peak was deconvoluted to two separated peaks located at 72.0 eV (blue) and 74.2 eV (red), representing tetrahedral Al 3+ and octahedral Al 3+ , respectively . The formation of these two different Al 3+ species may be caused by the different local oxygen abundance in the SnO 2 @Al 2 O 3 and the effect of Sn atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that the inversion degree depends significantly on the thermal history of the sample, which in general decrease with increasing temperature. 7,21,[49][50][51] The fact that the degree of inversion is dependent on thermal history has been reported for other spinel systems such as ZnFe2O4 and MgAl2O. 52,53 However, in most of these studies additional defects such as interstitials and vacancies are not taken into account.…”
Section: The Influence Of Heat Treatmentsmentioning
confidence: 98%
“…Zinc aluminate (ZnAl 2 O 4 ) spinel is a well-known wide band gap semiconductor (E g ¼ 3.8 eV) 1 ceramic material with optomechanical property, which has been extensively studied as a catalyst and catalyst support, [2][3][4] transparent conductor, 5 dielectric material, 6 optical material 7 and sensor 8 due to its high thermal stability, low surface acidity and high mechanical resistance. 9 Several methods, for example, the solid statereaction or ceramic method, 10 wet chemical routes, 11,12 the sol-gel method, 13,14 the hydrothermal method, 15 the solvothermal method, 16 the plasma method, 17 combustion in an aqueous solution 18 and molten salt synthesis 19 etc., have been applied for the preparation of ZnAl 2 O 4 spinel. However, to date, it is still a challenge to synthesize 2D or 3D ZnAl 2 O 4 spinel nanostructures via a solution route.…”
Section: Introductionmentioning
confidence: 99%